Rekonstruksi Strategi Branding Berbasis Artificial Intelligence di Era New Media - Achmad Arrosyidi; Mochammad Arifin; Hardman Budiardjo (CV. ITTC INDONESIA, 2026)
Branding in the new media era faces a strategic problem because consumer interactions are increasingly fragmented across digital platforms, while brands are required to deliver personalized, transparent, and authentic communication. This study aims to reconstruct a conceptual model of Artificial Intelligence (AI)-based branding strategy that explains the relationship between AI capability, digital branding strategy, customer experience, engagement, trust, and branding performance. The study applies a literature review approach using 25 core articles and 5 supporting references obtained from Scopus, ScienceDirect, SpringerLink, MDPI, Taylor & Francis, and Google Scholar. The analytical technique is thematic analysis conducted through literature identification, screening, relevance evaluation, data extraction, open coding, axial coding, theme classification, and conceptual synthesis. The findings show that AI capability is the most dominant theme; 18 of 25 core articles position data processing, prediction, automation, and personalization as the foundation of modern branding strategy. Other themes include AI-driven brand management, digital marketing and new media strategy, customer experience, brand engagement, brand equity, trust, ethics, transparency, generative AI content, and human-AI collaboration. The novelty of this article lies in an integrative model that places AI not merely as an automation tool but as a strategic branding capability controlled by ethical governance and human creativity.